Influence of Dehydration Temperature and Time on Physicochemical Properties of Tomato (Solanum lycopersicum L.) Powder - Degwale, Alemu; Asrat, Fentahun; Eniyew, Kefale; Asres, Derajew; Tesfa, Tiru; Ayalew, Asrat (Frontiers in Sustainable Food Systems, 2022)
The purpose of this research was to determine the optimum dehydration temperature and time length for a better physicochemical quality of tomato powders. The treatments consisted of 70, 80 and 90 oC dehydration temperatures and 9, 11 and 13 hours’ time durations arranged in a completely randomized design (CRD) with triplicates. The inlet and outlet air temperatures of the hot air oven dryer were about 24 and 60 oC respectively with an air velocity of about 2.9 m/s air velocity. Fresh tomatoes were used as a control. It has been observed that the major quality parameters of tomato powders were significantly increased with increasing dehydration temperature and time up to 80 oC and 11 hours respectively. When the dehydration temperature and time length went beyond 80 oC and 11 hours respectively, the quality of tomato powders declined. The maximum TSS content (7.433 oBrix), titratable acidity (0.4967), rehydration ratio (3.437), lycopene content (0.4512 mg/100g) and lower pH value (4.433) were obtained at 80 oC temperature and 11 hours dehydration time. Moisture content was reduced to 11% at the same dehydration temperature and time length without considerable physiochemical quality loss. Inversely, vitamin C was reduced as dehydration temperature and time increased. Generally, the results of this study showed that dehydration of tomatoes with 80 oC and 11 hours temperature and time length respectively, provides better physicochemical quality of tomato powders. Future research is suggested on consumers’ acceptance of dehydrated tomato powders.